Modulation of Liver Inflammation and Fibrosis by Interleukin-37 - Mountford, Steffeni; Effenberger, Maria; Noll-Puchta, Heidi; Griessmair, Lucas; Ringleb, Andrea; Haas, Sonja; Denk, Gerald; Reiter, Florian P.; Mayr, Doris; Dinarello, Charles A.; Tilg, Herbert; Bufler, Philip (Frontiers in Immunology, 2021)
Background and aims: Chronic inflammation induces liver fibrosis, cirrhosis and potentially liver cancer. Kupffer cells modulate hepatic stellate cells by secreting immunologically active proteins as TGF-β. TGF-β promotes liver fibrosis via the activation of Sma- and Mad-related protein 3. IL-37 broadly suppresses innate and adaptive immune responses. Intracellular IL-37 interacts with Smad3. We hypothesize that IL-37 downregulates the activation of hepatic Kupffer and stellate cells and interferes with the TGF-β signalling cascade to modulate liver fibrogenesis. Methods. The role of IL-37 on liver inflammation and fibrogenesis was assessed in three mouse models as well as isolated Kupffer- and stellate cells. Serum IL-37 was tested by ELISA in a clinical cohort and correlated with liver disease severity. Results. Transgene expression of IL-37 in mice extends survival, reduces hepatic damage, expression of early markers of fibrosis and histologically assessed liver fibrosis after bile duct ligation. IL-37tg mice were protected against CCl4-induced liver inflammation. Colitis-associated liver inflammation and fibrosis was less severe in IL-10 knockout IL-37tg mice. Spontaneous and LPS/TGF-β -induced cytokine release and profibrogenic gene expression was lower in HSC and KC isolated from IL-37tg mice and IL-37 overexpressing, IL-1β stimulated human LX-2 stellate cells. However, administration of recombinant human IL-37 did not modulate fibrosis pathways after BDL in mice, LX2 cells or murine HSCs. In a large clinical cohort, we observed a positive correlation of serum IL-37 levels with disease severity in liver cirrhosis. Conclusions: Predominantly intracellular IL-37 downregulates liver inflammation and fibrosis. The correlation of serum IL-37 with disease severity in cirrhosis suggests its potential as a novel target modulating the course of liver fibrosis.